The trust factor in the digital economy: Why privacy and security is fundamental for successful ecosystems - Rob van den Dam (International Telecommunications Society (ITS), 2017)
The volume of personal data collected by organizations is considerable and growing. But as more data is collected and transacted, the likelihood of a breach escalates. Cyberattacks are increasingly common and the volume and severity of data breaches and abuse continue to increase. With more and larger breaches in the news, consumers have become worried about – and suspicious of – the organizations that collect, store and use their data. And as digital ecosystems and the Internet of Things further expand, protecting customer data is more urgent than ever before.
Keywords: 330